A PROPÓSITO DEL ENFOQUE BCG - Esteves Dejo, Martha Cecilia (1992)
It raises some of the limitations of the Boston Consulting Group (BCG) method, a successful consulting product considered a simple tool that helps to comprehensively understand the decisions a company makes about its future. To this end, the validity of the concepts on which it is based, its goodness as an analysis tool and the applicability of its recommendations are discussed. The three central concepts that support the theoretical framework of the BCG are analyzed: the experience curve, the product life cycle and the portfolio balance, and the main objections to the strategic options derived from it are raised. The general propositions derived from the growth-participation matrix are discussed and two aspects are dealt with in detail: the validity of the strategy recommended by the BCG for "dog" businesses and the limitations that the product life cycle imposes on marketing managers.